Descriptive Epidemiology From the Research in Osteochondritis Dissecans of the Knee (ROCK) Prospective Cohort. Issue 1 (January 2022) - Nissen, Carl W.; Albright, Jay C.; Anderson, Christian N.; Busch, Michael T.; Carlson, Cathy; Carsen, Sasha; Chambers, Henry G.; Edmonds, Eric W.; Ellermann, Jutta M.; Ellis, Henry B.; Erickson, John B.; Fabricant, Peter D.; et al.
Background: Osteochondritis dissecans (OCD) occurs most commonly in the knees of young individuals. This condition is known to cause pain and discomfort in the knee and can lead to disability and early knee osteoarthritis. The cause is not well understood, and treatment plans are not well delineated. The Research in Osteochondritis Dissecans of the Knee (ROCK) group established a multicenter, prospective cohort to better understand this disease. Purpose: To provide a baseline report of the ROCK multicenter prospective cohort and present a descriptive analysis of baseline data for patient characteristics, lesion characteristics, and clinical findings of the first 1000 cases enrolled into the prospective cohort. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Patients were recruited from centers throughout the United States. Baseline data were obtained for patient characteristics, sports participation, patient-reported measures of functional capabilities and limitations, physical examination, diagnostic imaging results, and initial treatment plan. Descriptive statistics were completed for all outcomes of interest. Results: As of November 2020, a total of 27 orthopaedic surgeons from 17 institutions had enrolled 1004 knees with OCD, representing 903 patients (68.9% males; median age, 13.1 years; range, 6.3-25.4 years), into the prospective cohort. Lesions were located on the medial femoral condyle (66.2%), lateral femoral condyle (18.1%), trochlea (9.5%), patella (6.0%), and tibial plateau (0.2%). Most cases involved multisport athletes (68.1%), with the most common primary sport being basketball for males (27.3% of cases) and soccer for females (27.6% of cases). The median Pediatric International Knee Documentation Committee (Pedi-IKCD) score was 59.9 (IQR, 45.6-73.9), and the median Pediatric Functional Activity Brief Scale (Pedi-FABS) score was 21.0 (IQR, 5.0-28.0). Initial treatments were surgical intervention (55.4%) and activity restriction (44.0%). When surgery was performed, surgeons deemed the lesion to be stable at intraoperative assessment in 48.1% of cases. Conclusion: The multicenter ROCK group has been able to enroll the largest knee OCD cohort to date. This information is being used to further understand the pathology of OCD, including its cause, associated comorbidities, and initial presentation and symptoms. The cohort having been established is now being followed longitudinally to better define and elucidate the best treatment algorithms based on these presenting signs and symptoms.